ABO Blood Group and Risk of Thromboembolic and Arterial Disease: A Study of 1.5 Million Blood Donors. Issue 15 (12th April 2016) - Vasan, Senthil K.; Rostgaard, Klaus; Majeed, Ammar; Ullum, Henrik; Titlestad, Kjell-Einar; Pedersen, Ole B.V.; Erikstrup, Christian; Nielsen, Kaspar Rene; Melbye, Mads; Nyrén, Olof; Hjalgrim, Henrik; Edgren, Gustaf
Abstract : Background—: ABO blood groups have been shown to be associated with increased risks of venous thromboembolic and arterial disease. However, the reported magnitude of this association is inconsistent and is based on evidence from small-scale studies. Methods and Results—: We used the SCANDAT2 (Scandinavian Donations and Transfusions) database of blood donors linked with other nationwide health data registers to investigate the association between ABO blood groups and the incidence of first and recurrent venous thromboembolic and arterial events. Blood donors in Denmark and Sweden between 1987 and 2012 were followed up for diagnosis of thromboembolism and arterial events. Poisson regression models were used to estimate incidence rate ratios as measures of relative risk. A total of 9170 venous and 24 653 arterial events occurred in 1 112 072 individuals during 13.6 million person-years of follow-up. Compared with blood group O, non-O blood groups were associated with higher incidence of both venous and arterial thromboembolic events. The highest rate ratios were observed for pregnancy-related venous thromboembolism (incidence rate ratio, 2.22; 95% confidence interval, 1.77–2.79), deep vein thrombosis (incidence rate ratio, 1.92; 95% confidence interval, 1.80–2.05), and pulmonary embolism (incidence rate ratio, 1.80; 95% confidence interval, 1.71–1.88). Conclusions—: In this healthy population of blood donors, non-O blood groups explain >30% of venous thromboembolic events. Although ABO blood groups may potentially be used with available prediction systems for identifying at-risk individuals, its clinical utility requires further comparison with other risk markers. Abstract : Supplemental Digital Content is available in the text.